2016
DOI: 10.1002/chem.201603720
|View full text |Cite
|
Sign up to set email alerts
|

Tetraarylethylenes from Diarylmethanones and Hexachlorodisilane: The “Sila‐McMurry” Reaction

Abstract: Hexachlorodisilane reacts with diarylmethanones (aryl=C H , 4-MeC H , 4-tBuC H , 4-ClC H , 4-BrC H ) to furnish the corresponding tetraarylethylenes in good yields. The reductive conversion requires temperatures of about 160 °C and reaction times of 60-72 h. In the initial step, the Lewis-basic carbonyl groups likely generate low-valent [SiCl ] as an analogue of [TiCl ] in the classical McMurry reaction. The coupling sequence further proceeds via benzopinacolones, which have been isolated as key intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[2] In particular, reactions of silylenes with carbonyl compounds have received substantial attention because such reactions provide synthetically versatile oxasilacyles in a regio-and stereoselective manner and these reactions can be combined with the subsequent chemical transformations. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous studies have demonstrated three typical types of the reactions of silylenes with carbonyl compounds as illustrated in Figure 1: a) ene reactions to form silyl enol ethers A, b) (1 + 2) cycloadditions giving oxasiliranes B, and c) (1 + 4) cycloadditions to afford C. Reactions with an aryl aldehyde or an aryl ketone often furnish 5-methylene-1,3-cyclohexadiene (o-isotoluene) derivative D as a dearomatized cycloadduct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] In particular, reactions of silylenes with carbonyl compounds have received substantial attention because such reactions provide synthetically versatile oxasilacyles in a regio-and stereoselective manner and these reactions can be combined with the subsequent chemical transformations. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous studies have demonstrated three typical types of the reactions of silylenes with carbonyl compounds as illustrated in Figure 1: a) ene reactions to form silyl enol ethers A, b) (1 + 2) cycloadditions giving oxasiliranes B, and c) (1 + 4) cycloadditions to afford C. Reactions with an aryl aldehyde or an aryl ketone often furnish 5-methylene-1,3-cyclohexadiene (o-isotoluene) derivative D as a dearomatized cycloadduct.…”
Section: Introductionmentioning
confidence: 99%
“…Hence singlet silylenes have an ambiphilic nature and exhibit characteristic reactivity such as cycloaddition and insertion reactions for various substrates [2] . In particular, reactions of silylenes with carbonyl compounds have received substantial attention because such reactions provide synthetically versatile oxasilacyles in a regio‐ and stereo‐selective manner and these reactions can be combined with the subsequent chemical transformations [3–16] . Previous studies have demonstrated three typical types of the reactions of silylenes with carbonyl compounds as illustrated in Figure 1: a) ene reactions to form silyl enol ethers A , b) (1+2) cycloadditions giving oxasiliranes B , and c) (1+4) cycloadditions to afford C .…”
Section: Introductionmentioning
confidence: 99%
“… 30 Additionally, Moxter et al has successfully performed the “Sila-McMurry” coupling reaction using disilicon hexachloride in benzene-d 6 solution. 31 …”
Section: Coupling Reagents and General Proceduresmentioning
confidence: 99%
“…The deoxygenative dimerization of benzophenone derivatives using Si 2 Cl 6 as a reductant was reported by Wagner and coworkers ( Figure 15). 27 According to the known generation of the silyleneLewis base adduct, Cl 2 SiLB, via disproportiona-tion of Si 2 Cl 6 upon coordination of Lewis base, Cl 2 Si benzophenone adduct was proposed as a key intermediate. The coordination of a second benzophenone generates a fivemembered dioxasilolane intermediate, which upon the initial deoxygenation affords a benzopinacolone derivative.…”
Section: Transition-metal-free Reactionsmentioning
confidence: 99%